Nitrous oxide as a dynamical tracer in the 1987 Airborne Antarctic Ozone Experiment - Loewenstein, M.; Podolske, J. R.; Chan, K. R.; Strahan, S. E. (1989)
In situ N2O measurements were made using an airborne tunable laser absorption spectrometer (ATLAS) on 12 flights into the Antarctic vortex, as well as on five transit flights outside the vortex region in August and September 1987, as part of the Airborne Antartic Ozone Experiment. Vertical profiles of N2O were obtained within the vortex on most of these flights and were obtained outside the vortex on several occasions. Flights into the vortex region show N2O decreasing southward between 53 and 72 S latitude on constant potential temperature surfaces in the lower stratosphere. The data lead to two important conclusions about the vortex region: (1) the lower stratosphere in August/September 1987 was occupied by 'old' air, which had subsided several kilometers during polar winter; (2) the N2O profile in the vortex was in an approximately steady state in August/September 1987, which indicates that the spring upwelling, suggested by several theories, did not occur.